THE EFFECT OF USING PQ4R STRATEGY ON THE ABILITY OF THE SECOND YEAR STUDENTS OF MTS DARUL HIKMAH PEKANBARU IN COMPREHENDING RECOUNT TEXTS - Nina Fitriani; Supriusman Supriusman; Maria Safriyanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Absract: This research aimed to find out if there is a significant effect of using PQ4R strategy on the ability of the second year students of MTs Darul Hikmah Pekanbaru in comprehending recount texts. This research took place in MTs Darul Hikmah Pekanbaru, which was collected from February to March 2020. The try out class was VIIITQA2 class (19 students) and the sample was VIIIA3 (32 students) chosen by cluster random sampling. This is a pre-experimental research with one group pretest and posttest design. This research used quantitative data and the instrument used to collect the data was a reading test in multiple choice forms. As the result, the mean score of pre-test is 59.03 and post-test is 62.97. In the other words, the mean score of post-test is higher than the mean score of pre-test. The result also showed that the value of t-test (8.907) is higher than t-table (3.365) at the significance level 0.1%. It means that Alternative Hypothesis (Ha) is accepted. It can be concluded that there is a significant effect of using PQ4R strategy on the ability of the second year students of MTs Darul Hikmah Pekanbaru in comprehending recount texts. It is suggested that in understanding recount text is one of alternatives, the teacher needs to focus on the students’ understanding of the sentences on the texts.Key Words: Effect, Reading Comprehension, PQ4R Strategy